Topical Betamethasone Valerate 0.1% W/V vs. Topical Ketoconazole 2% W/V: A Comparison of Efficacy in Patients of Seborrheic Dermatitis - Rizwan, Muhammad; Ali, Amanat; Ahmed, Najia; Tahir, Moizza (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the efficacy of topical Betamethasone valerate 0.1% w/v and topical Ketoconazole 2% w/v in patients of seborrheic dermatitis.Study Design: Comparative prospective study.Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital Rawalpindi Pakistan from Feb to Aug 2019.Methodology: A total of 80 patients of both genders with seborrheic dermatitis were included. Patients were divided into two groups randomly, with 40 patients in each group. Group-A patients were given topical Betamethasone valerate 0.1% w/v, while patients in Group-B were given topical Ketoconazole 2% w/v for 12 weeks. Data regarding efficacy was assessed after 12 weeks per operational definition from both groups and noted.Results: The mean age of patients in group A was 34.45 ± 6.73 years, and in the Group-B was 32.18 ± 6.07 years. The majority of the patients, 54 (67.50%), were between 15 to 35 years of age. Efficacy of Group-A (topical Betamethasone valerate 0.1%) was seen in 35 (87.50%) patients while in Group-B (topical Ketoconazole 2%) efficacy was seen in 25 (62.50%) patients (p-value = 0.010).Conclusion: This study concluded that the efficacy of topical Betamethasone valerate 0.1% w/v is higher than topical Ketoconazole 2% w/v in patients with seborrheic dermatitis.